Jakość prowadzenia zajęć przez nauczycieli akademickich w ocenie studentów Akademii Wychowania Fizycznego oraz Uniwersytetu Ekonomicznego w Katowicach = The quality of teaching by lecturers in the evaluation of students of the Academy of Physical Education and University of Economics in Katowice - Socha, Paulina; Przybyła, Katarzyna (Journal of Education, Health and Sport, 2015)
Socha Paulina, Przybyła Katarzyna. Jakość prowadzenia zajęć przez nauczycieli akademickich w ocenie studentów Akademii Wychowania Fizycznego oraz Uniwersytetu Ekonomicznego w Katowicach = The quality of teaching by lecturers in the evaluation of students of the Academy of Physical Education and University of Economics in Katowice. Journal of Education, Health and Sport. 2015;5(11):669-677. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35717 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A669-677 http://pbn.nauka.gov.pl/works/684990 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Socha Paulina, Przybyła Katarzyna. Jakość prowadzenia zajęć przez nauczycieli akademickich w ocenie studentów Akademii Wychowania Fizycznego oraz Uniwersytetu Ekonomicznego w Katowicach. Quality in Sport. 2015;1(2):60-67. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Paulina Socha[1], Katarzyna Przybyła Akademia Wychowania Fizycznego w Katowicach Jakość prowadzenia zajęć przez nauczycieli akademickich w ocenie studentów Akademii Wychowania Fizycznego oraz Uniwersytetu Ekonomicznego w Katowicach The quality of teaching by lecturers in the evaluation of students of the Academy of Physical Education and University of Economics in Katowice Streszczenie Cel. Celem pracy było przedstawienie oczekiwań studentów względem swoich wykładowców w procesie dydaktycznym. Materiał i metody Badanie przeprowadzono metodą kwestionariuszową wśród studentów AWF oraz UE w Katowicach. Oceniano jakość kształcenia przy zastosowaniu 5-stopniowej skali Likerta. Podstawowe wyniki. Najwyżej cenionymi aspektami pracy wykładowców były posiadanie wiedzy praktycznej, umiejętność jej przekazywania oraz kompetencja. Wnioski. Badanie może przysłużyć się nauczycielom akademickim w celu wyrównania standardów i poziomu nauczania względem wymagań studentów. Słowa kluczowe: cechy nauczyciela akademickiego, oczekiwania studenta, pedagogika, Akademia Wychowania Fizycznego, Uniwersytet Ekonomiczny, Katowice. Abstract The aim of the study was to present the expectations of students towards their teachers in the teaching process . Material and methods. The study was conducted using the questionnaire method among students of Physical Education and the University of Economics in Katowice. Assessed the quality of education by using 5-points Likerts scale . Basic results. The most highly valued aspects of the work of lecturers were having practical knowledge, skill and competence of its transmission. Conclusions. The study may serve scholars to align standards and level of education relative to the requirements of the students. Key words: characteristics of the university teacher, student expectations, pedagogics, Academy of Physical Education, University of Economics, Katowice. [1] e-mail: paula_socha@interia.eu